2018
DOI: 10.1111/liv.13940
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid reprograms the liver to protect against hepatotoxicants, but is hepatotoxic at high doses

Abstract: Oleanolic acid (OA) is a triterpenoid that exists widely in fruits, vegetables and medicinal herbs. OA is included in some dietary supplements and is used as a complementary and alternative medicine (CAM) in China, India, Asia, the USA and European countries. OA is effective in protecting against various hepatotoxicants, and one of the protective mechanisms is reprogramming the liver to activate the nuclear factor erythroid 2-related factor 2 (Nrf2). OA derivatives, such as CDDO-Im and CDDO-Me, are even more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 106 publications
2
40
0
Order By: Relevance
“…When excessive xenobiotics, such as toxic drugs, chemicals, and viruses, cannot be eliminated in a timely manner, they can damage the liver (often by ROS), leading to acute or chronic liver injury [15][16][17]. CCl 4 is a toxic xenobiotic that causes hepatocyte necrosis and liver damage and is often used as a model toxin for the induction of liver injury and evaluating the protective effect of drugs [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…When excessive xenobiotics, such as toxic drugs, chemicals, and viruses, cannot be eliminated in a timely manner, they can damage the liver (often by ROS), leading to acute or chronic liver injury [15][16][17]. CCl 4 is a toxic xenobiotic that causes hepatocyte necrosis and liver damage and is often used as a model toxin for the induction of liver injury and evaluating the protective effect of drugs [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Though the hepatoprotective effect of OA has been well established, a recent study showed that repeated oral administration of OA induced cholestatic liver injury in mice [17] and OA altered bile acid homeostasis and produced cholestatic liver injury in C57 mice [18] . Thus, OA is effective in protecting against various hepatotoxicants at low dosages while higher dosages and long-term application could produce liver injury [19] . These observation provided evidence that OA could also be toxic to liver.…”
mentioning
confidence: 99%
“…However, it was recently observed that high dosage and long duration of OA treatment could induce liver injury in experimental mice [17,18] . Furthermore, this paradoxical hepatotoxic effect occurs not only for OA, but also for other OA-type triterpenoids [19] . Thus, in the present study, the cytotoxic effect of OA on LO2 hepatocytes were determined.…”
mentioning
confidence: 99%
“…The use of traditional medicines to modulate innate and adaptive immune functions has been reviewed [17]. Oleanolic acid, a triterpenoid from many herbs/fruits, could reprogram the liver to protect against a variety of hepatotoxicants at the low doses, but is hepatotoxic at higher doses [18]. Thus, learn to program the liver would help us to understand the bene cial or harmful effects of traditional medicines such as Hua-Feng-Dan.…”
Section: Introductionmentioning
confidence: 99%